Upaya Pengembangan Bakat Seni Tari melalui Kegiatan Ekstrakurikuler Tari di SD Negeri 10 Banda Aceh - Rheka Putri Meliza; Julia, Putry; Aswita, Dian (Universitas Negeri Medan, 2025)
This study aims to identify efforts to develop dance talent through extracurricular activities at SD Negeri 10 Banda Aceh. The background of this study is based on various obstacles such as the absence of special practice days and schedules, limited supervising teachers, inadequate facilities, and minimal school budget to support dance activities. This study uses a qualitative method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The subjects in the study consisted of the principal, one art teacher, and five students who have talent in dance. The study was conducted in the even semester of the 2024/2025 academic year. The results of the study indicate that the development of dance talent in this school has not been optimal. However, the principal has made efforts to provide a forum for art activities, while teachers play a role in providing motivation and opening up space for student exploration. Students show high enthusiasm, are able to express themselves, and begin to be confident in appearing in public. Therefore, further support is needed in the form of policies, facilities, and competent mentors so that extracurricular dance activities can run optimally and sustainably.